Ultrafine Particles Measurement in Printing Industry Across West Malaysia - Jamen, Shahrulnizam; Makmom Abdullah, Ahmad (International Journal of Engineering and Technology, 2018)
Ultrafine particles (UFPs) emission generated from devices such as printer and photocopy machines are known as potential risks to human health. However, limited information is available to study UFPs exposure generate from larger printer. Thus, this study aimed to determine the concentration of UFPs such as particle number (PN) and lung deposited surface area (LDSA) and investigates the influence of physical environment factors on UFPs in two types of offset lithographic printing rooms such as monochrome and color, across West Malaysia. The measurements of PN and LDSA were taken by using a condensation particle counter and the diffusion charger dosimeter during the printing activities. The mean values for PN and LDSA are 22215 particles/cm3 and 43 Âµm2/cm3, respectively. The exposure of UFPs from the monochrome room was found to be significantly higher than the color room (p < 0.001 for PN; p < 0.001 for LDSA) due to variation in the ventilation system. Based on correlation analysis, the physical environment factors, such as relative humidity, temperature, and air movement, were observed to influence the UFPs concentrations in printing room.Â The findings imply that a good selection of the ventilation system is important to minimize workerâ€™s exposure to UFPs emission. Â Â